Current status of tomato greenhouse production in Khartoum and Gezira States, Sudan. - Ibrahim, Sahar S.; Elamin, Osman M.; Elkashif, Mohammed E.; Abdalla, Abdalla S. (Gezira Journal of Agricultural Science, 2016)
Tomato production under protected cultivation has increased consistently in recent decades in the Sudan. The objective of this study was to investigate the current situation of tomato cultural practices in existing greenhouses in Khartoum and Gezira States. A survey was carried out using a questionnaire and interviews with greenhouse owners in Khartoum and Gezira States. Khartoum and Gezira States have about 68 greenhouse projects, 33 of them were selected for the study. Data were collected during 2013 and analyzed using statistical package for social sciences (SPSS). Results indicated that a large number of introduced tomato cultivars were used for production and most of greenhouse farmers (48.5%) sow tomato seeds in mid-February. The majority of farmers (63.6%) grow tomato in high plant density (30cm). More than half of greenhouses (75.8 %) had no specific fertilizer programs. Most of the greenhouse farmers (90.9 %) prune weekly. All greenhouse farmers used pesticides for pest control. Our observations indicated that most of the growers failed to produce summer tomato. Accordingly, further research in tomato greenhouse production is needed.